Core-shell Au@PtIr nanowires with dendritic alloy shells as efficient bifunctional catalysts toward methanol oxidation and hydrogen evolution reactions. (26th October 2021) - Wang, Xiaoqu; Qi, Jiuhui; Luo, Xinji; Yang, Zhongyun; Fan, Youjun; Jiang, Zhe; Liu, Chengzhou; Yang, Jun; Chen, Wei
Abstract: Nanocatalysts with combination of unique morphologies and synergistic interactions have a potential to enhance electrocatalytic ability related to the reactions in fuel cells. Here, we show a wet-chemistry-based synthesis of dendritic Au@PtIr nanowires (NWs) with core-shell constructions regarding Te NWs as sacrificial templates for methanol oxidation reaction (MOR) and hydrogen evolution reaction (HER). Regarding the synthesis of Au@PtIr NWs, Au NWs are firstly obtained through galvanic replacement with Te templates, followed by growth of alloy PtIr shells in subsequent seed-mediated growth. The as-synthesized core-shell Au@PtIr nanowires combine the advantage of one-dimensional (1D) dendritic feature that facilitate fast electron transport and provide more interfaces and interstices between catalytic active sites and electrolyte, with the synergistic interactions in alloy shells. Consequently, the as-prepared Au@PtIr NWs show good catalytic properties in MOR and HER in terms of higher activity, larger electrochemically active surface areas (ECSAs) and better anti-toxicity than commercial Pt/C. Graphical abstract: Core-shell Au@PtIr NWs with dendritic alloy shells were synthesized by combining galvanic replacement reaction with seed-mediated growth, which exhibit superior electrocatalytic properties for MOR and HER. Image 1 Highlights: Core-shell Au@PtIr nanowires (NWs) with are synthesized with Te NWs as sacrificial templates. The dendritic structure of the Au@PtIr NWs provide large surface area and facilitate fast mass transport. The Au@PtIr NWs show higher catalytic activity than Pt/C for the hydrogen evolution reaction. The Au@PtIr NWs are excellent electrocatalysts for methanol oxidation with high anti-toxicity.